Creative Destruction-or Just Destruction? Survival and Success in the Global Internet Economy - Cukor, Peter; Katz, Raul; McKnight, Lee W.; Vaaler, Paul M. (Tufts Archival Research Center, 2005)
Volume 24, Issue 1. Spring Identifying the key dynamics revolutionizing the field of telecommunications the authors suggest that a process of rapid innovation, followed by imitation, is eliminating the old industry structure and replacing it with a more dynamic, though more unpredictable, regime.